PERKEMBANGAN KESALAHAN DAN KEMAMPUAN BERTANGGUNGJAWAB DALAM PANDANGAN HUKUM PIDANA FORMIL - Triadi Triadi (Ensiklopedia Sosial Review, 2025)
Abstract: the ability to be responsible must exist: a) The ability to differentiate between good and bad actions in accordance with the law and those that are against the law; and b) The ability to determine one's will according to awareness of the good and bad of the action. An error is deemed to exist if intentionally or through negligence an act has been committed which causes a situation or consequence prohibited by criminal law and is carried out with responsibility. A person makes a mistake, if at the time of committing the offense, it is seen from the perspective of society. In this way, according to him, someone gets punished depending on two things, namely: there must be an act that is contrary to the law, or in other words, there must be an element of unlawfulness, so there must be an objective element, and for the perpetrator there is an element of error in the form of intent and/or negligence, so that the unlawful act can be held accountable to him. So there is a subjective element. No excuses. The relationship between the perpetrator and his actions is determined by the responsible ability of the perpetrator. The reason for forgiveness concerns the person of the perpetrator, in the sense that the person cannot be blamed or he is innocent or cannot be held responsible, even though his actions are against the law. On the other hand, there are reasons that eliminate the perpetrator's guilt, so that he is not punished.Keywords: Error, Ability, Formal.